Cigarette Smoke Induced Sural Nerve Dysfunction in Young Male Subjects (KYAMC Journal, 2025)
Background: Cigarette smoking has been attributed as a causative factor for many cardiovascular and respiratory diseases. Increasing evidence suggests that chronic smoking also alters neuronal function and can lead to neuronal injury in the peripheral nervous system. Sural nerve conduction study is an important electrodiagnostic test for early detection of peripheral nerve dysfunction. Objectives: To observe the effects of cigarette smoking on the electrophysiological status of the sural nerve in apparently healthy young male smokers. Materials and Methods: This case-control study was conducted in the Department of Physiology, Sir Salimullah Medical College, Dhaka, from July 2017 to June 2018. Thirty apparently healthy male cigarette smokers aged 25 to 40 years were included in the study group. Another thirty age, sex, and BMI matched non-smoker healthy subjects were controls. Nerve conduction parameters (latency, amplitude, and sensory nerve conduction velocity) of the sural nerve were studied by standard methods, using standard nerve conduction study and electromyography machine in the Department of Neurology, Dhaka Medical College Hospital. For statistical analysis, unpaired t test was done. Results: In this study, the latency of sural nerve was significantly prolonged (p ˂ 0.001), whereas amplitude and sensory nerve conduction velocity were significantly reduced (p ˂ 0.001) in cigarette smokers in comparison to non-smokers. Among the cigarette smokers, 20% showed evidence of subclinical impairment in sural nerve function. Conclusion: Chronic cigarette smoking causes dysfunction of sural nerve in young male subjects.